An Efficient Class of Repeated Measurements Designs to Control the Residual Effects Using Periods of Three Different Sizes - Javid Shabbir; Hafiz Muhammad Kashif Rasheed; Khadija Noreen; Abid Khan; Muhammad Adnan Ghani; Rashid Ahmed (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2023)
Repeated measurements designs (RMDs) are always economical but with the use of these designs, there may arise residual effects. Minimal strongly balanced RMDs are well known to estimate the treatment effects and residual effects independently. In the situation, where these designs cannot be constructed, minimal nearly strongly balanced RMDs are used which is an efficient class of RMDs to control the residual effects. In this article, efficient minimal circular nearly strongly balanced RMDs are constructed in periods of three different sizes.